2014
DOI: 10.2989/16085906.2014.927781
|View full text |Cite
|
Sign up to set email alerts
|

Love, lust and the emotional context of multiple and concurrent sexual partnerships among young Swazi adults

Abstract: Men and women in Swaziland who are engaged in multiple or concurrent sexual partnerships, or who have sexual partners with concurrent partners, face a very high risk of HIV infection. Ninety-four in-depth interviews were conducted with 28 Swazi men and women (14 of each sex) between the ages of 20 and 39 in order to explore participants’ sexual partnership histories, including motivations for sexual relationships which carried high HIV risk. Concurrency was normative, with most men and women having had at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Our findings reflect cross sections of the different relationship models which a woman may engage in over her life course, echoing previous research in Swaziland that describes men and women’s shifting priorities over time (Ruark et al, 2014). The main difference between the relationship models we identified is not the degree of economic dependence or sexual obligation --some degree of both appears to be the rule, rather than the exception – but the social acceptability of this tradeoff within a woman’s community.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings reflect cross sections of the different relationship models which a woman may engage in over her life course, echoing previous research in Swaziland that describes men and women’s shifting priorities over time (Ruark et al, 2014). The main difference between the relationship models we identified is not the degree of economic dependence or sexual obligation --some degree of both appears to be the rule, rather than the exception – but the social acceptability of this tradeoff within a woman’s community.…”
Section: Discussionsupporting
confidence: 85%
“…However, for women with less constrained agency in their relationships, the decision to forgo condoms with a sexual partner may be made based on personal preferences, and the decision is more likely to be made with agency, affection and trust. For many couples in Swaziland, southern Africa and the rest of the world, gift giving and financial support from a male partner are normative parts of courtship and relationships [ 13 , 26 , 64 , 65 ]. Research across the globe has shown that as intimacy and trust in a relationship increases, condom use decreases even in contexts with a high background HIV prevalence [ 66 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were interviewed three to five times between July 2013 and August 2014, with interviews lasting up to 90 minutes and each participant being interviewed for an average of three hours in total. Methods as well as findings from initial rounds of interviews are described in detail elsewhere (Ruark et al 2014). …”
Section: Methodsmentioning
confidence: 99%